Studies on Color Vision, Color Blindness, and Computer-Generated Images - Michael Ramek (Current Approaches in Science and Technology Research Vol. 4, 2021)
Around 8% of the male population and 0.4% of the female population have colour vision deficiencies. Since software design also operates along the coordinates red, green, and blue, computer generated images often create needless problems for those affected. The rainbow-like colour coding used in thermo-imaging and other applications is the subject of this research. There is an alternative to this rainbow spectrum.